Turning Smallness into Uniqueness : Six Key Challenges to Unlock Sao Tome and Principe Growth’s Potential - World Bank (World Bank, Washington, DC, 2019)
Economic growth in Sao Tome and Príncipe (STP) has long been driven by an unsustainable reliance on public expenditures, especially grant- and loan-financed public investment. STP needs to turn its smallness into uniqueness to unlock its growth potential. To accomplish this transformation, this image must be matched by a more balanced growth in which the private sector plays a larger role and with a more effective government. Tourism, agriculture, and fisheries could drive the country’s transition to a more balanced growth pattern. This Country Economic Memorandum (CEM) highlights six key challenges that STP must overcome as it transitions to a more balanced growth pattern and it offers policy recommendations for addressing each challenge. Accomplishing this rebalancing will require STP to address six key challenges at the macroeconomic, structural, and sectoral level. These include: (i) The twin budget and current-account deficits; (ii) Weak trade connectivity by both air and sea; (iii) Credit constraints caused by a high level of non-performing loans and difficulties enforcing commercial contracts; (iv) Uncertainty surrounding property rights and land tenure; (v) Poor-quality infrastructure, especially in the energy and transportation sector; and (vi) The overexploitation of marine resources.